The Effect of Professionalism and Interpersonal Communication on The Image of an Agency Through Public Trust as A Mediation Variable in The Tanjung Jabung Barat Resort Police - Haryadi Haryadi; M. Zahari; Ali Akbar (Siber International Journal of Digital Business (SIJDB), 2026)
This study aims to analyze the influence of professionalism and interpersonal communication on agency image through public trust as a mediating variable at the Tanjung Jabung Barat Police Resort. Police agency image reflects public perceptions of the performance, integrity, and quality of public services provided. This study employed a quantitative approach with a survey method. The study population was 11,200 individuals, including those who had received services from the Tanjung Jabung Barat Police Resort. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in a sample size of 100 respondents. Data were collected through a Likert-type questionnaire. Path analysis was used to examine the direct and indirect effects between variables. The results showed that professionalism and interpersonal communication had a positive and significant effect on public trust. Public trust also had a positive and significant effect on agency image. Furthermore, public trust was shown to mediate the influence of professionalism and interpersonal communication on agency image. These findings confirm that improving the professionalism and quality of interpersonal communication among police officers plays a crucial role in building public trust and strengthening the image of the police institution.